The Efficacy of Botulinum Toxin in Pediatric Chronic Migraine: A Literature Review. (October 2020) - Marcelo, Raymundo; Freund, Brin
Aims: To conduct a review of the literature on the use of botulinum toxin for the treatment of pediatric chronic migraine. Methods: A review of the literature was performed using EMBASE, PubMed, and Cochrane/Ovid. Using our inclusion and exclusion criteria, we targeted any study, published before April 2020, evaluating the efficacy of botulinum toxin in migraineurs younger than 18 years. Results: Seven studies were included: 2 retrospective analyses, 3 case series, a case report, and a randomized control trial. Studies included 1 to 125 patients, with the number of botulinum toxin treatments ranging from 1 to 11 treatments. The results of the randomized controlled trial showed nonsuperiority between placebo and botulinum toxin. Results of the other studies were generally favorable but were difficult to compare because of lack of standardization of botulinum toxin dosing, injection paradigm, frequency and duration of treatment, usage of accompanying prophylaxis, and variation in outcome measures across studies. There was low-quality evidence that botulinum toxin improved headache frequency and intensity, though some studies demonstrated efficacy in treatment with botulinum toxin. Conclusion: This review is the first of its kind, updating the literature on the efficacy of botulinum toxin in pediatric patients. Given evidence of its utility in treating pediatric migraines, off-label use should be considered in certain cases. Further study is warranted to better characterize injection paradigms and patient selection because of the limited and inconsistent data available.